2009
DOI: 10.1136/jnnp.2008.168211
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Parkinson's disease in Norway: the Norwegian ParkWest study

Abstract: Incidence rates of PD in Norway are similar to those in other Western European and American countries. Female gender was associated with a considerably lower risk of PD and slightly delayed motor onset but had no impact on severity of parkinsonism or clinical phenotype in incident drug naïve PD, suggesting that the female gender influences on the nigrostriatal system are most pronounced in the preclinical phase of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
213
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(225 citation statements)
references
References 41 publications
10
213
0
2
Order By: Relevance
“…Some studies, including our investigation, found a decline in incidence rates for the oldest old,14, 15, 16, 17, 18 and others did not 11, 12, 13. However, varying definitions and small sample sizes make comparisons difficult 1.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Some studies, including our investigation, found a decline in incidence rates for the oldest old,14, 15, 16, 17, 18 and others did not 11, 12, 13. However, varying definitions and small sample sizes make comparisons difficult 1.…”
Section: Discussionmentioning
confidence: 51%
“…Incidence rates are also low for those aged 50‐59 and increase sharply afterward. Age‐specific peaks differ between studies, however, ranging from 80.4 to 678 new cases/100 000 person‐years 11, 12, 13, 14, 15, 16, 17, 18, 19. German data on prevalence and incidence are rare, outdated, and had been designed primarily as door‐to‐door surveys 1.…”
Section: Introductionmentioning
confidence: 99%
“…The individuals with PD were obtained from the Norwegian Park West study, a prospective population-based cohort that has been described in detail [2]. Individuals with PD fulfilled the National Institute of Neurological Disorders and Stroke [15] and the UK Parkinson's disease Society Brain Bank [43] diagnostic criteria for the disease at their final visit.…”
Section: Patient Cohorts and Tissue Samplesmentioning
confidence: 99%
“…[1]. Bradykinesia or the of stuntment in movements, as main from the list of cardinal symptoms according to Brain Bank Criteria of UK Parkinson's Disease (BBC-UKPCD), was present in all respondents.…”
Section: Discussionmentioning
confidence: 99%